Integrated salt and water balance modelling for the management of waterlogging and salinization: Application of SaltCalc - SINGH, PRASHANT; MISHRA, ANIL KUMAR; JAISWAL, SMITA; KUMAR, LOVE (Journal of Soil and Water Conservation, 2024)
In Butana distributary of Western Yamuna Canal the twin problems of waterlogging and soil salinity have erupted due to over utilization of canal water; resulting into continuous rise of ground water table that is predominantly caused by the impaired drainage, altered geo-hydrological conditions and poor irrigation management apart from other minor reasons. SaltCalc model was calibrated and validated using measured data from the field and secondary data collected from the published literature. The calibrated values of the R2 and NSME were 0.83, 0.96, 0.93 and 0.91, 0.98, 0.91; respectively, for root zone salinity, transition zone salinity and water table depth from the SaltCalc model. The validated value of R2 and NSME were 0.85, 0.95, 0.92 and 0.89, 0.97, 0.96 for root zone salinity, transition zone salinity and water table depth meaning a very close fitting of observed and predicted parameters. Hence, SaltCalc model was used for scenario generation and prediction of future behaviour of the system. The ground water salinity might increase from 4.93 dS/m to 5.97 dS/m under the existing condition of soil salinity. With 100 per cent replacement of rice area with other crops like maize, sorghum and ragi; the water table might decline to 3.29 m below the ground surface against the existing 1.06 m in year 2026.Reducing the seepage from canal lining by 90 per cent, the ground water table might decline from exiting 1.06 to 1.765 m along with reduced ground water salinity from 4.95 dS m-1 to 4.21 dS m-1 after 11 years.